Sustainable and Environmentally Friendly Transportation: What We Can Learn For Indonesia - Zaini, Abdul Kudus (CSID Journal of Infrastructure Development, 2019)
Transportation has an important role in urban life. The urban transportation system used will affect the quality of the city, because of its related to the used of space, time and energy. Many problems are caused by transportation, such as air pollution, traffic congestion, high fuel consumption, traffic accidents, and so on. Transportation problems affect the survival of the surrounding environment. The relationship between transportation and the environment is very closely related, this relationship includes the development of transportation infrastructure or activities of transportation facilities that will have an impact that becomes an environmental change that uses transportation as access in supporting community activities both regarding the process and results of its activities. The link between transportation and the environment covers a very wide spectrum. The impact that can arise due to the existence of transportation infrastructure that physically affects the surrounding environment or due to the operation of the facility. To overcome transportation problems that damage the environment, it is necessary to have sustainable transportation development. Sustainable development in a global context is an economic and social development whose aim is to improve, not damage environmental conditions. Challenges in implementing sustainable transportation programs include the complexity of urban environmental transportation problems and the high conflicts of interests and social implementation in the field, diverse cultural structures and social class of awareness within the community and the lack of human resources.